Absolute beginner's guide to Microsoft Windows Vista - O'Hara, Shelley (Que, 2006)
Absolute Beginners Guide to Windows Vista Absolute Beginner's Guide to Microsoft® Windows Vista will have you using your computer and new Windows operating system in no time! Here's a small sample of what you'll find inside: Describes how to get going: starting programs, creating and saving documents, printing, and using your computer for both productivity and play! Covers connecting to, browsing, and searching the Internet as well as how to send and receive email. Learn how to use the networking tools of Windows Vista to connect with any other computers in your home. Explains how to use the new Windows Photo Gallery to organize, edit, and print your pictures. Details security precautions you can take to prevent viruses, protect against malicious programs, and keep email secure. Provides advice on how to maintain tip-top performance and organization for your work. Highlights exciting multimedia features including listening to music, recording your own CDs, and sampling new tunes. Absolute Beginner's Guide to Microsoft® Windows Vista teaches you how to get started with Windows (and computing in general). The book starts with the fundamentals and then builds on these skills in a smooth and effortless manner. The authors walk you through the process using a hands-on approach, covering topics that include starting programs, sending email, browsing the Internet, downloading music, and printing documents and pictures. Not only will you learn the nuts and bolts of using Windows, but you'll also receive a crash course in additional topics, like security and home networking, that will improve your computing experience. Absolute Beginner's Guide to Microsoft® Windows Vista provides valuable, practical advice and instruction that you will refer to again and again. Shelley O'Hara is the author of more than 120 books, most of which relate to computers. She specializes in books that explain technical concepts and features, and writes in terms that the beginning user can understand. A former trainer, Shelley worked in the publishing industry before becoming a full-time writer. She has written some of the best-selling and most popular computer books on the market, including Easy Windows XP, Home Edition and Easy Windows 98. Ron Mansfield is a best-selling author with more than 30 books under his belt, including eBay to the Max and Launching a Successful eBay Store. He is also an eBay and computer consultant and instructor.